1988
DOI: 10.1007/bf02005821
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute iron loading on contractility and spontaneous beating rate of cultured rat myocardial cells

Abstract: Cardiac dysfunction is a well known but poorly understood complication of iron overload. We have previously shown that cultured myocardial cells are able to assimilate large amounts of iron. In the present study, the effect of iron on the rate and amplitude of beating in monolayer cultures of rat ventricular myocytes was studied. Iron had negative chronotropic and inotropic effects, both reversible upon washout. The negative chronotropic effect developed earlier and could be reversed by adrenaline. The negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…37 Conversely, α‐tocopherol, a natural lipid‐soluble antioxidant, is able to interrupt the chain reaction of membrane lipid peroxidation initiated by free radicals and to interfere with iron‐induced lipid peroxidation in liposomes. 19,20,36 Finally, as shown in our heart cell culture studies, deferoxamine removes iron directly from iron‐loaded heart cells, inhibits lipid peroxidation, 16–19 and reverses the abnormalities in cellular contractility and rhythmicity induced by iron.…”
Section: Role Of Ntpi In Myocardial Diseasementioning
confidence: 59%
“…37 Conversely, α‐tocopherol, a natural lipid‐soluble antioxidant, is able to interrupt the chain reaction of membrane lipid peroxidation initiated by free radicals and to interfere with iron‐induced lipid peroxidation in liposomes. 19,20,36 Finally, as shown in our heart cell culture studies, deferoxamine removes iron directly from iron‐loaded heart cells, inhibits lipid peroxidation, 16–19 and reverses the abnormalities in cellular contractility and rhythmicity induced by iron.…”
Section: Role Of Ntpi In Myocardial Diseasementioning
confidence: 59%
“…Our previous studies in cultured rat heart cells have shown that the rate of low molecular weight iron uptake is more than 300 times that of transferrin iron [18]. Such uptake results in increased myocardial lipid peroxidation leading to impaired mitochondrial inner membrane respiratory enzyme activity, damage to sarcolemmal thiolic enzymes such as 5 0 -nucleotidase and Na,K-ATPase [28], and abnormal contractility [29,30]. These effects are reversed by in vitro treatment with DFO [16,29].…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Cultures were kept at 37°C in an atmosphere of 5% CO 2 and 95% air in Ham F-10 medium containing added 1 mM CaCl 2 , 10% fetal calf serum, and 10% horse serum. The rat cardiomyocyte H9C2 cell line was grown in 5% CO 2 in air in Dulbecco modified Eagle (DMEM) medium supplemented with 10% fetal calf serum, 4.5 g/L D-glucose, glutamine, and antibiotics (all from Biological Industries, Kibbutz Bet Haemek, Israel).…”
Section: Cell Culturesmentioning
confidence: 99%